On Passband and Stopband Cascaded-Integrator-Comb Improvements Using a Second Order IIR Filter - Alfonso Fernandez-Vazquez; Gordana Jovanovic Dolecek (Universitas Ahmad Dahlan, 2012)
This paper proposes an efficient second order IIR filter which considerably improves the passband as well as the stopband of the cascaded-integrator-comb (CIC) filter. Using the polyphase decomposition of the proposed filter, all filtering can be moved to a lower rate, which is D times less than the high input rate, where D is the decimation factor. The overall phase response of the compensated CIC is approximately linear in the passband. The design parameters are the number of cascaded CIC filter N, the decimator factor D, the passband frequency wp, and a weighted parameter a.